2000
DOI: 10.1093/clinchem/46.10.1535
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Polymorphism Influences Iron Status in Blacks

Abstract: Background: Genetic variants of human transferrin (TF) have been described, but little is known about their functional differences. We studied iron status according to TF phenotype in a healthy Zimbabwean population and in subjects at risk of African iron overload. Methods: The study population consisted of 483 nondrinkers, 31 drinking spouse pairs, and 5 family pedigrees (n = 88) with index cases of iron overload. TF phenotypes were determined using starch gel electrophoresis. To evaluate iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…The p-value very close to the threshold of statistical significance deserves to be confirmed on a larger sample population or on a population of heterogeneous tuberculosis from several sites in order to favor a random distribution of the Hp alleles. This result disagrees with those of the Kasvosve et al (2000) study on tuberculosis patients High positive (1 to 3 cross) microscopies were found in groups of Hp1-1 and 2-1 phenotypes but this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The p-value very close to the threshold of statistical significance deserves to be confirmed on a larger sample population or on a population of heterogeneous tuberculosis from several sites in order to favor a random distribution of the Hp alleles. This result disagrees with those of the Kasvosve et al (2000) study on tuberculosis patients High positive (1 to 3 cross) microscopies were found in groups of Hp1-1 and 2-1 phenotypes but this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…These two results indicated the same trend which was similar to those of Kaminskaia, Abdullaev, Elufimova, Mitinskaia, and Iukhimenko (2004) and Philemond et al (2017). However, they differed from what reported by many previous studies in which the Hp2-2 phenotype is less protective and therefore more expected to be found in patients than in controls (Langlois & Delanghe , 1996, McDermid & Prentice , 2006Kasvosve et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Common polymorphisms in the haptoglobin gene (HP) or in mitochondrial DNA have been associated with more severe iron overload phenotypes in some studies [31,32] but not in other reports [19,33,34]. Transferrin mutations influence serum iron measures in sub-Saharan blacks, but do not appear to be associated with most cases of iron overload [19,35,36]. A mutation in the ironresponsive element of the ferritin heavy-chain gene (FTH1) accounted for iron overload in some members of a Japanese family [37].…”
Section: Discussionmentioning
confidence: 99%
“…No samples were found that encompassed Tf-BB or Tf-DD variants. Identification of genetic variants by CZE is straightforward provided that the resolution of the Tf isoforms is sufficient [29,30,42,80,81,83,118,126,142,144,145]. It is easiest done with spiking the unknown sample with a serum of a known variant and reanalysis of the mixture [142].…”
Section: Genetic Variants Of Tfmentioning
confidence: 99%